Habituation Model in Forming Character Religious at SMP Negeri 1 Gatak - Rahayu, Aprillia Cebbing Ageng; Istanto, Istanto (Journal of Educational Sciences, 2025)
This study aims to describe the habituation model in forming the religious character of students at SMP Negeri 1 Gatak. Using a qualitative descriptive approach, data were collected through interviews with Islamic Religious Education teachers, the Vice Principal for Student Affairs, and students, and strengthened by direct observation in the school environment. The results of the study indicate that SMP Negeri 1 Gatak applies various models of religious habituation, such as Al-Qur'an Reading and Writing (BTA) activities, Friday morning recitation, congregational prayers, use of amaliyah books, and habituation of discipline and tolerance. All of these activities involve the active role of teachers, student organizations (Pionir/Rohis), and the entire school community, so that a religious and conducive learning environment is created. Although there are challenges in optimizing religious character, the innovation and collaboration carried out by the school prove that religious character education can be implemented effectively in public schools through a structured and sustainable habituation model.